Case Report: Hematoma Formation After Spontaneous Coronary Artery Rupture - Liang, Weitao; Yue, Honghua; Zhang, Tailong; Wu, Zhong (Frontiers in Cardiovascular Medicine, 2022)
We report a case of hematoma formation in the right coronary artery after spontaneous rupture. The 48-year-old female was admitted with right cardiac mass at first, despite a thorough examination, there was still diagnostic uncertainty as to the nature of the mass. The patient underwent an exploration surgery where the mass was partially incised on a beating heart, and thrombus-liked tissue can be found inside without bleeding. We described the challenges during the diagnose process, and the diagnosis was finally made according to a multimodality approach. For further assessment, we reviewed related literature and highlighted the importance of coronary artery angiography in the preoperative evaluation of such patients. The therapy varies according to different locations and severity of the lesion.